UNSUR-UNSUR CINTA DALAM ANTOLOGI CERPEN TERE LIYE “BERJUTA RASANYA” - Rohmah, Rina Ari (Universitas Hamzanwadi, 2021)
This study aims to describe the elements of love in Tere Liye's anthology of the short stories Berjuta Rasanya. The phenomenon that often occurs is the elements of love that only apply to the opposite sex, not in general. However, this research tries to reveal the elements of love in general through the author's depictions of the characters. This type of research is a qualitative descriptive study using a literary psychology approach. The data source in this study is the anthology book by Tere Liye published by Mahaka Publishing in 2015. The data used are in the form of sentences and paragraphs. The data collection techniques used in this study were library techniques, reading techniques, and note taking techniques. Data validation was carried out by theoretical triangulation. The results showed that there are eight types of love elements contained in the short story anthology Berjuta Rasanya by Tere Liye, which consists of: passionate love, eros love, altruistic love, sacred love, manic love, maternal love, romantic love, and self-love. Of the eight elements of love, the most dominant in the short story anthology is love mania.